Effect of Boiling on Total Phenolics and Antioxidant Activity (DPPH And ABTS) of Carica Papaya Flower Ethanolic Extracts - Khadijah Khadijah; Merlin Merlin; Ahmad Muchsin Jayali; Artati Artati; Wa Reti La Maca; Wa Andini Ariyani; Sarni Sarni; Ikram Hamid (Direktorat Politeknik Kesehatan Makassar, 2026)
Carica papaya flowers are widely found in North Maluku, Indonesia, and have potential as a source of phenolic compounds with antioxidant activity. However, information on the effect of boiling on their phytochemical profile and bioactive properties is still limited. This study aimed to compare the phytochemical profile, total phenolic content, and antioxidant activity of ethanol extracts from raw and boiled C. papaya flowers. Fresh flowers were prepared as raw and boiled samples at 90°C for 10 min, then extracted with ethanol. Qualitative phytochemical screening was carried out, total phenolic content was determined using the Folin-Ciocalteu method, and antioxidant activity was evaluated using DPPH and ABTS assays in triplicate. The qualitative phytochemical profile of both extracts showed the presence of alkaloids, flavonoids, phenolics, steroids, terpenoids, and saponins. Boiled C. papaya flower extract had higher total phenolic content than raw extract, with mean values of 14.42 mg TAE/g and 8.05 mg TAE/g, respectively. Boiled extract also showed stronger antioxidant activity, with lower IC5050​ values in the DPPH assay (197.99 mg/L vs. 289.31 mg/L) and ABTS assay (94.37 mg/L vs. 134.48 mg/L). These results suggest that boiling may enhance the release of phenolic compounds and improve the antioxidant potential of C. papaya flowers. Further studies using compound identification, statistical validation, and in vivo testing are needed to confirm these findings and support their application in functional food development.